Contaminação microbiana das soluções de processamento radiográfico: Risco de infecção cruzada - Jardim Júnior, Elerson Gaetti [UNESP]; Jardim, Ellen Cristina Gaetti [UNESP]; Schweitzer, Christiane Marie [UNESP]; Landucci, Luis Fernando; Salzedas, Leda Maria Pescinini [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2011)
Objective: To evaluate the microbial contamination in samples of radiographic developing and fixing solutions, radiographic processing water, dental unit waterlines and dental office's external water supply. Methods: Samples of 50 private dental offices and 20 dental offices of the School of Dentistry de Araçatuba-UNESP were collected. The samples were subjected to neutralization of the residual inhibitory agents followed by pre-enrichment in peptone water and EVA broth and were inoculated in selective and non-selective culture media. The DNA of the samples was extracted and the presence of superinfectant microorganisms was evaluated by PCR. The differences in the prevalence of the microorganisms in the samples of the solutions were analyzed by repeated-measures analysis of variance for category data, while the Chi-Square and Mann-Whitney tests were used to evaluate the existence of associations between the total number of heterotrophic microorganisms and infection control protocols. The significance level was set at 5%. Results: Samples of radiographic fixing solution presented a remarkably less frequent contamination than radiographic developing solution and radiographic processing water. The latter exhibited microorganisms typically originated from the oral microbiota and human skin as well as microorganisms frequently found in dental unit waterlines. There was less contamination of radiographic processing water in the dental offices where the x-ray film packets were disinfected before processing or were covered by a plastic film. Additionally, all samples of dental office's external water supply were drinkable. Conclusion: Covering the x-ray film packets with a plastic film protection barrier was proven the best manner to reduce the contamination of the evaluated solutions.
Microbial contamination of radiographic developing and fixing solutions: Risk of cross infection
Keywords: Infection control; Prevention; Radiology